Aortic root wrapped procedure. (12th October 2011) - Wenbin, Li; Shiqiu, Song; Zifan, Zhou; Lu, Li; Hanping, Guo; Quansheng, Cao; Sheng, Wang; Zhouyi, An; Anxin, Liu; Jianqing, Zhang
Abstract : Objective: To develop a relatively simple and effective and less risk operation, aortic root wrapped procedure, to treat with aortic root aneurysm or ectasia. Methods: From June 2008 to September 2010, 15 patients were accepted of aortic root wrapped angioplasty procedure, Marfan's syndrome with aortic root ectasia in 2 case, and aortic sinus aneurysm with middle – severe aortic valve stenosis and/or regurgitation in 13 cases. The diameter of aortic valve annulus: 25.43±2.34 (22–32) mm, the diameter of aortic sinus: 50.45±7.32 (45–60) mm. All patients undertook aortic root wrapped angioplasty procedures combined with aortic valve plasty or replacement with tissue valve prosthesis. Results: 15 patients were survival well, and the peri-operative mortality was 0%. CBP time was 82.31±16.34 (55–128) min. Predischarge UCG check result was showed: trace aortic regurgitation in 3 cases, and normal aortic valve function in 12 cases; Comparing with preoperative UCG results, aortic annulus diameter 22.63±1.25 (21–25) mm, decreased significantly (p<0.01), aortic sinus diameter 36.86±7.41 (30–41) mm, decreased significantly (p<0.001). Follow-up results: All 15 patients were survival well, and Heart function (NYHA) of the patients are all Class I. The late mortality was 0%. Conclusion: Aortic root wrapped procedures combined with aortic valve plastic or replacement operation is an alternative surgical procedure in patients with aortic sinus aneurysm and aortic valve disease.